Samozatajni pjesnik s Novoga Zelanda - Kalogjera, Branka (Array, 2008)
We find the poet Frane Pervan in such prestigious anthologies as the Wellington International Poetry Festival 2004, and in the leading New Zealander poetry journal Poetry NZ, edited by well-known publisher Alistar Patterson, whose publishing policy focuses on presenting talented immigrants and the most celebrated poets of New Zealand, Australia and the USA. That fact is indubitable proof of Pervan's incontrovertible artistic value. A poet equally skilled in expressing himself both in the Croatian and English languages, Frane Pervan (5 May 1939, Kokorići, Vrgorac - 12 August 2007, Auckland) was a member of the Writer's Society of New Zealand and a member of many years of the Croatian-Australian Literary and Art Society in Sydney. Regarded in the context of contemporary New Zealander literature, in which he was present as both poet and prose writer, Pervan proved himself as a modern, urban poet, a man who felt the pulse of the land in which he lived and which served him as the basis of many poetic inspirations. Based on an analysis of the New Zealander literary scene we can assert that Frank Pervan was an indubitably well-known and recognised name not only in New Zealand, but also outside its borders. The magazines in which we have found the poet Pervan, namely, are distributed in Australia, Great Britain and the USA, and a recent English literary award is proof of his international acclaim.